THE 24-HOUR KNOWLEDGE FACTORY: CAN IT REPLACE THE GRAVEYARD SHIFTS. - Gupta, Amar (Computer (00189162), 2009)
This article discusses the design of work systems that take advantage of time zone differences to enable 24 hour production schedules in locations distributed around the world. The distribution of workflow around the world to enable 24-hour services or information management is described. The separation of testing and software development responsibilities within a single 24-hour workday is described. The use of scrum-like communication systems to indicate changes made by individual developers is noted. Issues relating to communication between collaborators working on a project around the world are described.